The Challenge of DNA Barcoding Saproxylic Beetles in Natural History Collections—Exploring the Potential of Parallel Multiplex Sequencing With Illumina MiSeq - Sire, Lucas; Gey, Delphine; Debruyne, Régis; Noblecourt, Thierry; Soldati, Fabien; Barnouin, Thomas; Parmain, Guilhem; Bouget, Christophe; Lopez-Vaamonde, Carlos; Rougerie, Rodolphe (Frontiers in Ecology and Evolution, 2019)
Saproxylic beetles are important bioindicators of forest health but their enormous diversity makes their identification challenging. As an example, the French fauna of saproxylic beetles alone contains 2663 species in 72 families. Recently, DNA barcoding was proposed as a promising tool for the identification and monitoring of saproxylic beetle species. However, the rate of DNA barcode recovery from specimens of natural history collections using standard Sanger sequencing protocols remains low and challenges the construction of reference libraries. In this study, we test the potential of high-throughput sequencing (HTS) technology to reduce this shortfall by increasing sequencing success rate and lowering processing cost per specimen. Using a dual-indexing strategy for library construction and sequencing on the Illumina MiSeq platform, we successfully sequenced the DNA barcodes of 286 dry-pinned saproxylic beetles out of 521 specimens aged from one to 17 years and sampled in natural history collections. Age at sequencing did not affect sequence recovery and the success rate (54.9%) of our approach is comparable to that obtained using Sanger sequencing technology in another study targeting beetle specimens from natural history collections, but the cost per specimen is significantly reduced when using HTS. Finally, we shortly discuss how the newly produced DNA barcodes contribute to the existing library and we highlight a few interesting cases in which the new sequences question current species boundaries.